2015
DOI: 10.1002/adma.201501604
|View full text |Cite
|
Sign up to set email alerts
|

7.7% Efficient All‐Polymer Solar Cells

Abstract: By controlling the polymer/polymer blend self-organization rate, all-polymer solar cells composed of a high-mobility, crystalline, naphthalene diimide-selenophene copolymer acceptor and a benzodithiophene-thieno[3,4-b]thiophene copolymer donor are achieved with a record 7.7% power conversion efficiency and a record short-circuit current density (18.8 mA cm(-2)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
367
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(376 citation statements)
references
References 49 publications
8
367
0
1
Order By: Relevance
“…If small molecules appear highly promising in particular through their 3D-edifice building ability [91,92], the best photovoltaic performances are still achieved with n-type copolymers. In particular, polymers using the strong electron withdrawing naphthalene di-imide (NDI) unit in the conjugated backbone have shown high electron mobilities and strong absorption between 500 and 750 nm, leading to high PCEs in all polymer solar cells [15,93]. As discussed previously in this review, due to its strong electronegativity, the addition of fluorine atoms along the conjugated backbone allows the lowering of both FMO energy levels.…”
Section: N-type Fluorinated Polymersmentioning
confidence: 93%
See 1 more Smart Citation
“…If small molecules appear highly promising in particular through their 3D-edifice building ability [91,92], the best photovoltaic performances are still achieved with n-type copolymers. In particular, polymers using the strong electron withdrawing naphthalene di-imide (NDI) unit in the conjugated backbone have shown high electron mobilities and strong absorption between 500 and 750 nm, leading to high PCEs in all polymer solar cells [15,93]. As discussed previously in this review, due to its strong electronegativity, the addition of fluorine atoms along the conjugated backbone allows the lowering of both FMO energy levels.…”
Section: N-type Fluorinated Polymersmentioning
confidence: 93%
“…Also, the fluorinated derivatives of the PTB7 polymer series (see Figure 1), which were designed following the pro-quinoïdal approach, achieved a PCE above 10% [13,14]. Jenekhe et al demonstrated a PCE of 8% in all polymer solar cells using PTB7 as electron donor material [15,16]. Last but not least, fluorination has also turned out to be efficient in designing highly performing molecular semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the power conversion efficiency (PCE) of “polymer:nonfullerene” solar cells with nonfullerene‐type electron acceptors has reached ≈11–13% by introducing polymer donors with bithienylbenzodithiophene (BDTT)‐based units and nonfullerene acceptors with indacenodithienothiophene (IT)‐based derivatives 15, 16, 17, 18, 19. However, less attention has been paid to applying such interfacial layers for polymer:nonfullerene solar cells, particularly for the inverted‐type device structures that benefit from the use of stable top electrodes with high work functions including, e.g., silver (see Table S1 in the Supporting Information) 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30…”
Section: Introductionmentioning
confidence: 99%
“…These properties of the polymer/polymer blend system are greatly beneficial for future applications in portable and wearable devices that require both high performances and mechanical stability [1]. Therefore, polymer/polymer blend solar cells have recently received considerable attention and significant strides have been made in improving their power conversion efficiencies (PCEs) [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%